1985
DOI: 10.1002/app.1985.070301214
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of polymer melts in high shear rate

Abstract: SynopsisLittle is known of the rheology of polymer melts in the high shear rate up to 106 s-1 or more. A specially designed high-shear-rate rheometer was developed, by which the rheology of polymer melts for shear rates up to 108 s-l can be investigated. Two non-Newtonian regions and a transition or the second Newtonian region were observed in the wide range of shear rates up to lo7 s-l . The observed flow curves for various polymer melts are classified into three typical patterns. One is the flow curve typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 1 publication
0
15
0
2
Order By: Relevance
“…(9). Takahashi et al72 have carried out experiments to measure the viscosity of pure PS melt at very high shear rates (up to 10 8 s −1 ) using a specially designed high‐shear‐rate rheometer. They observed that the second Newtonian region was not observed for PS melts, instead a transition region was observed over which dual values of the apparent viscosity were obtained at one shear rate.…”
Section: Modeling Of Thermophysical Propertiesmentioning
confidence: 99%
“…(9). Takahashi et al72 have carried out experiments to measure the viscosity of pure PS melt at very high shear rates (up to 10 8 s −1 ) using a specially designed high‐shear‐rate rheometer. They observed that the second Newtonian region was not observed for PS melts, instead a transition region was observed over which dual values of the apparent viscosity were obtained at one shear rate.…”
Section: Modeling Of Thermophysical Propertiesmentioning
confidence: 99%
“…A second Newtonian plateau for the PP and HDPE melts was also observed by Rides et al at the shear rates of above 2 × 10 6 s −1 . Takahashi et al observed not only a second Newtonian plateau at the shear rate of above 3 × 10 6 s −1 but also a second shear thinning region at the shear rate of above 7 × 10 6 s −1 for the HDPE melt. For the polystyrene (PS) melt, Kelly et al and Rides et al found the shear thickening behavior at the shear rates of above 5.0 × 10 5 and 3.6 × 10 5 s −1 , respectively.…”
Section: Introductionmentioning
confidence: 98%
“…The polymer melts are subjected to complicated rheological history featuring higher shear rates (over 10 6 s 21 ) during injection molding, especially micro-injection molding [1][2][3][4]. However, there is still a lack of knowledge of high-shear-rate rheology of polymer melts [5][6][7][8][9][10][11][12], especially its comparison for different polymers under high shear rates [8][9][10][11][12]. Haddout et al [8,9] found that the polypropylene (PP) and high-density polyethylene (HDPE) melts follow pseudoplastic shear thinning behavior at the shear rates of up to 10 6 s 21 , above which their shear viscosity curves reach a quasi-Newtonian plateau.…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of further extending the measuring range to a much higher level (e.g. 10 5 –10 7 s −1 ), the online capillary rheometers have been developed based on the injection‐molding machine [2–4]. It is worthy to note that under high shear rates or high pressures, the increasing influences of the end pressure loss, pressure dependence of the melt viscosity, dissipative heating, and melt compressibility on the capillary flow may evidently affect the reliability of the rheological measurement [5, 6], provided that no proper treatments are applied.…”
Section: Introductionmentioning
confidence: 99%
“…A few of works have been carried out to characterize the high‐shear‐rate rheological behavior of polymer melt [2–4, 18]. Under the shear rates of about 10 6 s −1 , the degradation of polymer [2], the second Newton plateau [2–4], and shear thickening behavior [4] were observed. Nevertheless, to the best knowledge of the authors, there is a lack of reports on the systematical analyses for the aforementioned four effects in capillary rheology under high shear rates, which may be responsible for the unique rheological behaviors.…”
Section: Introductionmentioning
confidence: 99%